Lack of Association of the HMGA1 Gene Variants with Metabolic Syndrome Risk and Response to Oral Anti-Diabetic Drugs - Faiq , Mirna K.; Saleh, Eman S.; Fathalla, Omar B. (AL-Kindy College Medical Journal, 2023)
Background: Metabolic syndrome (Mets) is partially heritable. High mobility group AT-hook1 (HMGA1), an architectural transcription factor, affects the homeostasis of glucose. The marked inter-individual differences between T2DM patients in response to oral anti-diabetic drugs have become an issue for effective prescribing and dosing. The objective of this study was designed to assess whether different SNPs of the HMGA1 gene are associated with metabolic syndrome, and clarify the effect of these variants on response to combination therapy of metformin, sitagliptin, and glimepiride used by Mets with diabetes patients. Methods: From February until Augusts 2022, a total of 91 Iraqi participants (61 patients with metabolic syndrome and 30 controls). The diabetes patients were divided into two groups’ responders and non-responders, based on their HbA1c. Polymorphisms in HMGA1 and genotyping were identified by Sanger sequencing of genomic DNA. Results: The high prevalence of CC and GG genotypes of rs1023028442 and rs112081775 respectively was seen in the Iraqi population. Minor allele frequency of rs1023028442 was higher among metabolic patients without diabetes with (MAF=0.08) compared to the control group with (MAF= 0%). While (MAF=0.1) of rs112081775 was seen in metabolic patients without diabetes compared to (MAF=0.02) in the control group. The non-significant difference in genotyping and allele carriage frequencies of the HMGA1 gene was seen between total metabolic syndrome patients and the control group. Based on their response to therapy non-significant difference was seen between those with wild and carrier genotypes. Conclusions: This study suggests a lack of association of the rare HMGA1 gene variants with metabolic syndrome risk and response to oral anti-diabetic drugs.